Study of Laparoscopic Inguinal Hernia Repair Using an Anatomically Contoured 3D Mesh - Mangam, Nilesh; Gosaliya, Dhaval (Asian Journal of Medical Sciences, 2021)
Background: Laparoscopic inguinal hernia surgery frequently is performed with mechanical fixation of polypropylene mesh. This mechanical fixation, though is necessary to prevent mesh migration, may be associated with pain syndromes and buckling. Recently an anatomically contoured 3D mesh (developed by Dr. Philippe Pajotin) has been introduced which is made up of monofilament polypropylene and resembles normal inguinal area curvature. Aims and Objective: This study was conducted to know whether elimination of tacking the 3D mesh during Total extraperitoneal approach (TEP) inguinal hernia repair results in decreased postoperative pain without increasing the incidence of hernia recurrence. Materials and Methods: This was a prospective interventional study in which 63 patients with clinical diagnosis of inguinal hernia were included on the basis of a predefined inclusion and exclusion criteria. All selected patients underwent laparoscopic TEP inguinal hernia repair using anatomically contoured 3D mesh. Patients were assessed for postoperative pain (using visual analogue scale) during their stay in the hospital as well as in the followup period. Results: In this study of Lap aroscopic inguinal hernia surgery using anatomically contoured 3D mesh of 63 male patients the most common affected age group was found to be 41-50 years (25.3%) with a mean age of 47.12 years +/- 13.01. Most common inguinal hernia was of indirect type (50.7%) and was seen on right side (52.3%). Mean operative time was 113.57+/- 29.04 minutes in unilateral and 170.6 ± 5.85 minutes in bilateral inguinal hernias. Postoperative mean VAS score (12 hrs) was found to be 3.46 ± 1.51. During follow up at 1 week, 1 month and 3 months mean VAS scores were found to be 0.46 ± 0.50, 0.14 ± 0.35 and 0.01 ± 0.12 respectively. Common complications included seroma (12.6%), pneumoscrotum (7.9%) and peritoneal breech (6.3%). None of the patients developed recurrence during follow up period. Conclusion: An anatomically contoured mesh for laparoscopic preperitoneal hernia repair usually requires no fixation and has minimal complications. It is associated with excellent recovery and marked reduction in pain.